Combined Treatments Reduce Chilling Injury and Maintain Fruit Quality in Avocado Fruit during Cold Quarantine - Sivankalyani, Velu; Feygenberg, Oleg; Maorer, Dalia; Zaaroor, Merav; Fallik, Elazar; Alkan, Noam (PLOS ONE, 2015)
Quarantine treatment enables export of avocado fruit (Persea americana) to parts of the world that enforce quarantine against fruit fly. The recommended cold-based quarantine treatment (storage at 1.1°C for 14 days) was studied with two commercial avocado cultivars ‘Hass’ and ‘Ettinger’ for 2 years. Chilling injuries (CIs) are prevalent in the avocado fruit after cold-quarantine treatment. Hence, we examined the effect of integrating several treatments: modified atmosphere (MA; fruit covered with perforated polyethylene bags), methyl jasmonate (MJ; fruit dipped in 2.5 μM MJ for Hass or 10 μM MJ for Ettinger for 30 s), 1-methylcyclopropene (1-MCP; fruit treated with 300 ppb 1-MCP for 18 h) and low-temperature conditioning (LTC; a gradual decrease in temperature over 3 days) on CI reduction during cold quarantine. Avocado fruit stored at 1°C suffered from severe CI, lipid peroxidation, and increased expression of chilling-responsive genes of fruit peel. The combined therapeutic treatments alleviated CI in cold-quarantined fruit to the level in fruit stored at commercial temperature (5°C). A successful therapeutic treatment was developed to protect ‘Hass’ and ‘Ettinger’ avocado fruit during cold quarantine against fruit fly, while maintaining fruit quality. Subsequently, treated fruit stored at 1°C had a longer shelf life and less decay than the fruit stored at 5°C. This therapeutic treatment could potentially enable the export of avocado fruit to all quarantine-enforcing countries. Similar methods might be applicable to other types of fruit that require cold quarantine.